How Destination Branding Moderates the Relationship between Destination Antecedents and Tourist Resonance: Evidence from a Philippine Destination - Mark Justine Vicera; Beatrice Cruz (Research Synergy Foundation, 2025)
This study examined the impact of destination antecedents on destination tourist resonance, with a focus on Coron, Palawan, Philippines. Anchored in the Tourist-based Brand Equity model, the research examined how destination salience, destination performance, and imagery, tourist judgements and feelings influence tourist loyalty and emotional connections, with destination performance & imagery and tourist judgments & feelings serving as mediators. The study also evaluated the moderating role of destination branding in these relationships. Employing an explanatory-quantitative research design, data were collected through structured surveys administered to 280 sample tourists who visited Coron, Palawan, Philippines. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze the structural relationships between the constructs. The findings indicate that destination salience significantly affects destination performance and imagery, and destination tourist resonance. Destination performance and imagery, along with tourist judgments and feelings, were found to mediate the relationship between destination salience and destination tourist resonance, highlighting the importance of both cognitive and emotional evaluations. Destination branding, on the other hand, significantly moderated the relationship between destination performance, imagery, and destination tourist resonance. However, the moderating role of destination branding showed no significant impact on destination salience and destination tourist resonance, suggesting the need for more cohesive branding strategies. This research addressed gaps in the application of brand equity models to emerging destinations and provided insights for enhancing localized branding strategies.